2022
DOI: 10.1590/1678-4162-12708
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and health care profiles of dogs and cats associated with the socioeconomic profile of their tutors in areas assisted by Family Health Strategies in Brazil

Abstract: This study aimed to evaluate the demographic and healthcare situation of dogs and cats owned by families assisted by the Family Health Strategy (FHS), from Santa Maria/RS, Brazil. This research was a cross-sectional and population-based study developed by applying a questionnaire to residents in the 16 FHS areas of the city. This was the first study addressing pet animal conditions in the FHS area. A total of 414 households were studied, and 88.5% of them had pets (dogs and/or cats), with an average of 2.2 dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
2
4
0
1
Order By: Relevance
“…This study provides the first estimates of cat sex frequencies in Uruguay, and the first carried out at the level of the entire country in Latin America. The fact that in Uruguay, the female sex is more frequent than the male sex in cats coincides with some reports from other countries (Australia: [10]; Italy: [11]; Brazil; [27,28] and Ethiopia: [50]), while other studies have found no differences in the frequency of male and female cats (Brazil: [44]; As for the presence of cat breeds in Uruguay, the most common breed is the Siamese (86%), with the remaining 14% being distributed among the Persian (8.9%), Ragdoll (1.4%), Maine Coon (1.4%), Himalayan (0.7%), Bombay (0.7%), and Bengal (0.7%) breeds (Chi-Square = 623, df6, p < 0.01). There was no significant association between breeds and sex (Chi-Square = 7.56, df6, p = 0.27).…”
Section: Sex Age and Spay/neuter Statussupporting
confidence: 88%
See 4 more Smart Citations
“…This study provides the first estimates of cat sex frequencies in Uruguay, and the first carried out at the level of the entire country in Latin America. The fact that in Uruguay, the female sex is more frequent than the male sex in cats coincides with some reports from other countries (Australia: [10]; Italy: [11]; Brazil; [27,28] and Ethiopia: [50]), while other studies have found no differences in the frequency of male and female cats (Brazil: [44]; As for the presence of cat breeds in Uruguay, the most common breed is the Siamese (86%), with the remaining 14% being distributed among the Persian (8.9%), Ragdoll (1.4%), Maine Coon (1.4%), Himalayan (0.7%), Bombay (0.7%), and Bengal (0.7%) breeds (Chi-Square = 623, df6, p < 0.01). There was no significant association between breeds and sex (Chi-Square = 7.56, df6, p = 0.27).…”
Section: Sex Age and Spay/neuter Statussupporting
confidence: 88%
“…This suggests that the frequency of cats by sex can vary according to the different geographical This study provides the first estimates of cat sex frequencies in Uruguay, and the first carried out at the level of the entire country in Latin America. The fact that in Uruguay, the female sex is more frequent than the male sex in cats coincides with some reports from other countries (Australia: [10]; Italy: [11]; Brazil; [27,28] and Ethiopia: [50]), while other studies have found no differences in the frequency of male and female cats (Brazil: [44]; EE.UU. : [51]; Australia and New Zealand: [33]; Great Britain [32]) or that males were more frequent than females (Colombia: [41]; Chile: [40]; EE.UU: [52]; Netherlands [3]).…”
Section: Sex Age and Spay/neuter Statussupporting
confidence: 88%
See 3 more Smart Citations